Orthotopic living related donor transplantation of the liver right lobe in the treatment of unresectable bilobular liver metastases from colorectal cancer - Kotenko, O. H.; Kotenko, I. O.; Hryhorian, M. S.; Minich, A. A.; Mykhailiuk, O. S.; Matvienkiv, A. O. (Zaporozhskiĭ medit͡s︡inskiĭ zhurnal, 2023)
Aim. Тo study the treatment result of unresectable liver metastases from colorectal cancer by the technique of transplantation. Case report. A man, born in 1963, applied to the Medical Center “Universal Clinic “Oberig” with a diagnosis of rectal adenocarcinoma pT3bN0M1 (hep) G2, synchronous colorectal liver metastases with multifocal bilobar lesions, stage IV after laparoscopic rectal extirpation and adjuvant FOLFIRI + Cetuximab polychemotherapy. Following a thorough examination of the patient, a decision was made to treat by transplanting a liver lobe graft donated by a living related donor (son). On April 12, 2022, the patient underwent orthotopic living related donor transplantation of the liver right lobe. In the early postoperative period, the patient developed an acute perforated ulcer of the small intestine, and he therefore was reoperated. The postoperative period was severe, but the condition stabilization was achieved with conservative treatment, and on the 38th postoperative day, the recipient was discharged from the hospital in a satisfactory condition. According to the control abdominal MRI during follow-up examinations, no signs of recurrence or progression were detected, however, 2 isolated metastatic foci in the lung parenchyma were detected bilaterally on the control CT scan of the chest 11 months after the liver lobe transplantation from the living related donor. Resection of metastatic foci was performed and systemic polychemotherapy was prescribed in that regard. Based on the control laboratory and instrumental examinations from 05.05.2023 (CT scan, MRI), there were no signs of the disease recurrence, the level of carcinoembryonic antigen was 1.5 ng/ml. Conclusions. Liver transplantation is an effective and radical method of treatment for patients with unresectable liver metastases from colorectal cancer. Transplantation using liver lobe from a living related donor in unresectable isolated liver metastases from colorectal cancer has advantages over all other methods and is safe for donors in highly specialized centers with sufficient experience in living related liver transplantation.